1999
DOI: 10.1002/(sici)1097-4636(199908)46:2<262::aid-jbm16>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nitride coating on titanium to enable titanium-ceramic bonding

Abstract: Failures that occur in titanium-ceramic restorations are of concern to clinicians. The formation of poorly adhering oxide on titanium at dental porcelain sintering temperatures causes adherence problems between titanium and porcelain, which is the main limiting factor in the fabrication of titanium-ceramic restorations. To overcome this problem a 1-microm thick Si3N4 coating was applied to a titanium surface using a plasma-immersion implantation and deposition method. Such a coating serves as an oxygen diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Ceramic coatings on metal substrates have therefore been suggested for the bearing components of joint replacements, including coatings of titanium nitride (TiN), diamond like carbon (DLC), chromium nitride (CrN), chromium carbon nitride (CrCN) and zirconium oxide (ZrO 2 ) [15][16][17][18]. Deposition processes for silicon nitride coatings for biomedical and other applications outside human body have also been described [19][20][21][22]. These processes include chemical vapour deposition (CVD) [20], ion-assisted deposition (IAD) [23], plasma immersion ion implantation and deposition (MPIID) [19], physical vapour deposition (PVD) [21,22] and plasma spray coating techniques [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic coatings on metal substrates have therefore been suggested for the bearing components of joint replacements, including coatings of titanium nitride (TiN), diamond like carbon (DLC), chromium nitride (CrN), chromium carbon nitride (CrCN) and zirconium oxide (ZrO 2 ) [15][16][17][18]. Deposition processes for silicon nitride coatings for biomedical and other applications outside human body have also been described [19][20][21][22]. These processes include chemical vapour deposition (CVD) [20], ion-assisted deposition (IAD) [23], plasma immersion ion implantation and deposition (MPIID) [19], physical vapour deposition (PVD) [21,22] and plasma spray coating techniques [24].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition processes for silicon nitride coatings for biomedical and other applications outside human body have also been described [19][20][21][22]. These processes include chemical vapour deposition (CVD) [20], ion-assisted deposition (IAD) [23], plasma immersion ion implantation and deposition (MPIID) [19], physical vapour deposition (PVD) [21,22] and plasma spray coating techniques [24]. Each technique exhibits advantages and disadvantages, for example plasma sprayed coatings present poor adhesion to the substrate while silicon nitride films produced with CVD results in hydrogenated films [16,22].…”
Section: Introductionmentioning
confidence: 99%
“…These processes include physical and chemical vapor deposition [14][15][16][17][18] , ion-assisted deposition (IAD) 19) , plasma immersion ion implantation 20,21) , laser surface alloying 22) , thermal oxidation 23) , sol-gel technique [24][25][26][27][28] , and plasma spray coating techniques 24,29,30) . Each technique presents both advantages and disadvantages 24) .…”
Section: Introductionmentioning
confidence: 52%
“…This has been demonstrated in studies that evaluated titanium surface alterations [23][24][25][26]29,[32][33][34][36][37][38][39][40][41][42][43] and also in studies that did not adopt the ISO standard methods, e.g. those of Sadeq et al [39], Oshida & Hashem [40], Wang and co-workers [41,42], Könönen & Kivilahti [43], Hanawa et al [44], Papadopoulos et al [45], and Cai et al [46]. From these studies it can be concluded that bond strength can be improved not only passively-by hindering oxide formation-but also actively, by adding to the process components that facilitate the bond between the veneering porcelain and the titanium framework.…”
Section: Discussionmentioning
confidence: 95%